Words and Silence in Job Mentoring - Joaquin Solana; Carmen Ruiz-Viñals (Ignatianum University Press, 2021)
Today, economic sustainability is a social priority and it implies positive, rewarding, and creative relationships in the workplace. Creativity, innovation, and subjective welfare will remain extremely important for sustainable production models in an age of technological acceleration, ecological threats, and digital globalization. With the impact of the COVID-19 pandemic and the new ways to organize work, this is even more important. The basis for this is to be found in education, especially in secondary and higher education. Good mentoring is becoming essential in professional development; this activity is based on words and silence, using corporate and individual coaching tools to open new doors of creativity. Following Peter Drucker's (1954) work in management thinking and the approach of positive psychologists, this paper presents a new concept of sustainable working relationships for the 21st century based on words and narratives.